NOISE LEVEL INVESTIGATION (L-MIN AND L-MAX) IN PRINTING LABORATORY AT POLITEKNIK NEGERI MEDIA KREATIF, JAKARTA - Antinah Latif (Politeknik Negeri Media Kreatif, 2019)
Printing is one of the activities that have job risks for its workers. One of the risks of works in printing is the presence of physical environment factors. This study aims to determine the noise level with different types of machines in the printing lab at Politeknik Negeri Media Kreatif, Jakarta. The study design used in this research is descriptively obtained through direct measurements using Sound Level Meters in digital printing work areas, Computer to Print machines (pre-press), 4 color sakura brand printing machines (press), and production machines in the post-press machine that is a folding, cutting machine, wire sewing machine, binding machine, and press machine. Obtained an average of different noise levels each section under 85 dBA tolerated by law.